Efficiency transfer method applied to surface beta contamination measurements. (April 2018) - Stanga, D.; De Felice, P.; Capogni, M.
Abstract: In this paper, the application of the efficiency transfer method to the evaluation of the surface beta contamination is described. Using efficiency transfer factors, the reference calibration factor of contamination monitors is corrected, to obtain the calibration factor for an actual contamination source. The experimental part of the paper illustrates the applicability of the method to the direct measurement of the surface beta contamination. Highlights: Efficiency transfer method is applied to surface beta contamination measurements. Efficiency transfer factors are computed by Monte Carlo method. Efficiency transfer factors are computed using the available information on sources. Calibration factor of contamination monitors is corrected using transfer factors.